Temperature Effect on Vibrational Frequency and Ground State Energy of Strong-Coupling Polaron in Symmetry Rbcl Quantum Dots (Journal of Atomic and Molecular Sciences, 2014)
By employing the linear combination operator and the unitary transformationmethods, we study the vibrational frequency and the ground state energy of astrong-coupling polaron in symmetric RbCl quantum dots (SRQDs). The effects of thetemperature and the confinement strength are taken into account. It is found that thevibrational frequency and the ground state energy are increasing functions of the temperatureand the confinement strength. We find two ways of tuning the vibrationalfrequency and the ground state energy via adjusting the temperature and the confinementstrength.
Keywords: vibrational frequency; linear combination operator; temperature effect; unitary transformation methods; Polaron.